Diseases of the musculoskeletal system and approaches to their treatment - Kulasharova Muxlisa Zokir qizi (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2024)
The incidence of musculoskeletal and connective tissue diseases (MSCTD) was studied in 2 categories of individuals: adults of working age and adults older than working age. A comparative analysis of the primary incidence of MCTD diseases was conducted. The dependence of the nosology on the age group was established. A number of preventive measures were proposed to reduce the overall incidence among the adult population.